The Effects of Resistance Training on Bone Mineral Density in Postmenopausal Women – A Review of Current Evidence - Tabian, Alicja (Journal of Education, Health and Sport, 2025)
Introduction and objective: Osteoporosis is a major public health problem among postmenopausal women, which is featured with decreased bone mineral density (BMD) and high fracture risk. The objectives of the present review is to address the impact of resistance exercise on BMD in postmenopausal women and to evaluate the potential mechanotransduction pathways needed for osteoporosis prevention. Review methods: All data were collected from publicly available sources. This article’s databases were accessed via PubMed, Scopus, and Web of Science. A brief description of the state of knowledge: Recent research shows that estrogen is crucial in maintaining bone homeostasis, and its absence post-menopause accelerates bone resorption. Muscle mechanical loading via resistance training increases bone remodeling and improves BMD. Aerobic exercises along with resistance training together serve as a better approach in improving bone density and overall physical fitness. Specifically, in fracture-prone areas like the femoral neck, where high-intensity resistance training can have a significant effect on increase in BMD. Summary: The findings of this paper indicate that resistance training is effective in preventing osteoporosis among postmenopausal women. Exercises with high resistance like deadlifts and squats improve BMD in the lumbar spine, hips and femoral neck. And, by adding resistance exercises as a part of an overall exercise regimen for postmenopausal women, we can be sure that they are noticeably maintaining their bone health and quality of life. More research is needed to unlock best training protocols and personalized significance.